Population Structure of Saltwater Crocodile (Crocodylus porosus) from Sarawak River Basin, Sarawak using Microsatellite and mtDNA Approaches - Reymathi, Nadarajan (Univerisiti Malaysia Sarawak, 2023)
This study is designed to determine the genetic variations and genetic population structure among Crocodylus porosus in 13 Sarawak River Basin (RB) using microsatellite and mtDNA approaches. Relationships between saltwater crocodiles in Sarawak RB using 13 microsatellite markers were estimated. Out of the 52 samples amplified, one marker (Cj35) was polymorphic and showed double bands, whereas the other seven markers revealed a single band (Cj127, Cj131, Cj122, Cj101, Cj119, CUD68 and Cj16) and five markers revealed multiple bands. In addition, geographical distances do not influence genetic distances when microsatellite loci were used. DNA microsatellite divides the crocodile samples into four clades: A, B, C and D. Combined sequence data of Cytochrome Oxidase I gene (579 bp) and Cytochrome b gene (913 bp) had shown that Crocodylus porosus is monophyletic. Six out of ten haplotype shows unique haplotype (Hap_2, Hap_3, Hap_6, Hap_7, Hap_8 and Hap_10). Further analysis showed that there is gene flow between 12 populations from different RB based on values of nucleotide diversity (π) and number of migrants (Nm) values. Based on AMOVA value, this study also recorded that within population is higher than among population. The findings also revealed that population could be divided into northern, central, and western groupings based on geographical population location rather than RB. Future research should involve more samples representing all 22 RB in Sarawak so that a more comprehensive understanding on the genetic structure of crocodile in Sarawak. The findings from this study is hoped to shed lights on the genetic structure and diversity of saltwater crocodiles in RB and could be used by relevant agencies to carry out sustainable management of wild crocodile population in Sarawak.